Comparative Efficacy of Antihypertensive Drugs for Primary Stroke Prevention–A Network Meta-Analysis of Randomized Controlled Trials - Dessy Natalia; Leo Deddy Pradipta; Adwin Alamsyaputra (Universitas Pelita Harapan, 2025)
Introduction: Hypertension is a major modifiable risk factor for stroke, making antihypertensive therapy essential for primary stroke prevention. However, the comparative efficacy of different antihypertensive drug classes remains uncertain. This study aims to evaluate the comparative efficacy of various antihypertensive drug classes in reducing the risk of stroke in patients with hypertension through a network meta-analysis of randomized controlled trials (RCTs). Methods: A search was conducted using various online databases, including PubMed, Google Scholar, Scopus, and ScienceDirect, to identify RCTs which were written in English and published before January 2025. A network meta-analysis was performed to compare the effectiveness of different drug classes, including angiotensin-converting enzyme inhibitors (ACEIs), angiotensin receptor blockers (ARBs), calcium channel blockers (CCBs), beta-blockers, and diuretics in stroke primary prevention. Independently, two reviewers (D.N. and L.D.P.), extracted the data and assess the quality of studies using Cochrane RoB 2.0. Results: This analysis included 43 RCTs involving 255299 participants with hypertension. Among the evaluated drug classes, non-dihydropyridine CCB demonstrated the highest efficacy in stroke prevention (RR 0.61; 95%CI 0.48 – 0.77), followed by dihydropyridine CCB (RR 0.62; 95%CI 0.54 – 0.72). Most of the studies had decent quality assessment with moderate heterogeneity across them with I2 = 39%. Egger’s test showed nonsignificant results (p= 0.16), suggesting the absence of publication bias in the included trials. Conclusion: This meta-analysis showed that calcium channel blocker emerges as the most effective option for reducing stroke risk, but considerations of adverse effects and individual patient profiles remain critical in treatment selection.